ANALISIS EFEKTIFITAS PENGGUNAAN ANGGARAN BELANJA LANGSUNGTERHADAP ANGGARAN BERBASIS KINERJA PADA KANTOR KECAMATAN PAMEKASAN - Mohammad Herman Djaja (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
This research illustrates the effectiveness of the use of direct budgetary towards performance-based budgeting at pamekasan subdistrict office, Regency of Pamekasan. Based on the ratio comparation of the budgetary utilization effectiveness at Pamekasan subdistrict Office in 2009 showed that the Program of  Office Administrative Services, Program of Facilities and Infrastructure Apparatus Improvement. Program of Apparatus Resource Capacity  Improvement, Program Intensify the Society Complaint Handling, Program of Planning New Autonomous Region, Programs of District Administrative Services  said effective according to the effectiveness ratio reaching 100%. Then the ratio comparation of the budgetary utilization effectiveness at Pamekasan subdistrict Office in 2010 showed that Program of Office Administrative Services, Program of Facilities and Infrastructure Apparatus Improvement. Program of Apparatus Resource Capacity  Improvement, Program Intensify the Society Complaint Handling, Program of Planning New Autonomous Region, Programs of District Administrative Services said effective according to the effectiveness ratio reaching 100%. Next, direct expenditure contribution to expenditure budget total at Pamekasan subdistrict Office in 2009 and in 2010 there are some activities that are necessary to be done the increase , among others, as follows: Program of Facilities and Infrastructure Apparatus Improvement, Program of Apparatus Resource Capacity  Improvement, Program Intensifies the Society Complaint Handling, Program of Planning New Autonomous Region, Program of District Administrative Services.